Thallium-induced DNA damage, genetic, and epigenetic alterations - Sánchez-Chapul, Laura; Santamaría, Abel; Aschner, Michael; Ke, Tao; Tinkov, Alexey A.; Túnez, Isaac; Osorio-Rico, Laura; Galván-Arzate, Sonia; Rangel-López, Edgar (Frontiers in Genetics, 2023)
Thallium (Tl) is a toxic heavy metal responsible for noxious effects in living organisms. As a pollutant, Tl can be found in the environment at high concentrations, especially in industrial areas. Systemic toxicity induced by this toxic metal can affect cell metabolism, including redox alterations, mitochondrial dysfunction, and activation of apoptotic signaling pathways. Recent focus on Tl toxicity has been devoted to the characterization of its effects at the nuclear level, with emphasis on DNA, which, in turn, may be responsible for cytogenetic damage, mutations, and epigenetic changes. In this work, we review and discuss past and recent evidence on the toxic effects of Tl at the systemic level and its effects on DNA. We also address Tl’s role in cancer and its control.